Staphylococcus epidermidis biofilms control by N-acetylcysteine and rifampicin - Leite, Bruna; Gomes, Fernanda; Teixeira, Pilar; Souza, Clovis; Pizzolitto, Elisabeth [UNESP]; Oliveira, Rosário (Wolters Kluwer, 2013)
Medical device-associated infections caused by Staphylococcus epidermidis usually involve biofilm formation and its eradication is particularly challenging. Although rifampicin has been proving to be one of the most effective antibiotics against S. epidermidis biofilms, its use as a single agent can lead to the acquisition of resistance. Therefore, we assessed the combined effect of rifampicin with N-acetylcysteine (NAC) known by its mucolytic effect, in the control of S. epidermidis biofilms. Biofilms of 2 S. epidermidis strains (9142 and 1457) were treated with 1× minimum inhibitory concentration (4 mg/mL) and 10× minimum inhibitory concentration (40 mg/mL) of NAC and 10 mg/L (peak serum) of rifampicin alone and in combination. NAC at 40 mg/L alone or in combination with rifampicin (10 mg/L) significantly reduced (4 log 10) the number of biofilm cells. Considering their different modes of action, the association of NAC with rifampicin constitutes a promising therapeutic strategy in the treatment of infections associated to S. epidermidis biofilms. © 2013 Lippincott Williams & Wilkins.
Keywords: Biofilm; N-acetylcysteine; Planktonic cells; Rifampicin; Staphylococcus epidermidis; acetylcysteine; mucolytic agent; rifampicin; bacterial strain; biofilm; controlled study; device infection; drug effect; minimum inhibitory concentration; mucolysis; nonhuman; priority journal